Academic Writing: Training and Assistance in writing scientific papers for prospective Mathematics teachers - Ani Afifah; Supriyo Supriyo; Andika Setyo Budi Lestari (Jurnal Dedikasi, 2023)
One of the primary objectives of education is to facilitate the cultivation and realization of an individual's inherent capabilities and talents. Human resource development (HR) is a key aspect of development policy within the education sector. Its primary objective is to enhance the academic capabilities and professional competence of teachers while also ensuring improved welfare provisions for educators. Teachers are required to exhibit a consistent level of professionalism in the execution of their responsibilities, including the essential skill of doing scholarly research. Empirical evidence indicates that many educators continue to require support in scientific publication production and implementation. Consequently, there is a pressing need for targeted and well-organized help to address this requirement. Hence, the primary objective of this service initiative is to offer support to aspiring teacher candidates while also fostering the motivation of teaching faculty to engage in writing and assembling scholarly publications. The employed methodologies encompass analysis, observation, mentoring, training, and assessment. The training program emphasizes developing skills in composing Classroom Action Research (PTK) reports through instructional techniques such as lectures, question-and-answer sessions, discussions, and simulations. The outcomes of this endeavour provide advantages to the individuals undergoing instruction, as it enhances their comprehension and proficiency in composing scholarly publications.